ANALISIS KUANTITATIF KANDUNGAN MERKURI (Hg) PADA PRODUK BEDAK PEMUTIH YANG BEREDAR DI KOTA BATAM: QUANTITATIVE DETERMINATION OF MERCURY (Hg) LEVELS IN WHITENING POWDERS DISTRIBUTED IN BATAM CITY - Mayefis, Delladari; Marliza, Hesti; Maharani, Refina (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Cosmetics are ingredients or mixtures of ingredients to be used on parts of the human body with the intention of cleansing, protecting to keep it in good condition and can play a role in healing and skin care. Facial cosmetic products that are currently often used are powder. There are various forms of powder, one of which is whitening powder which is widely discussed not only the product that floods the market, but also because of the impact of using the product which is able to whiten and brighten the face in a very short time. The content contained in these products also varies, some are formulated safe to use and dangerous when used. One of them is that mercury (Hg) is usually added intentionally or not very unjustified because it will be in direct contact with the skin and can be toxic. This study aims to identify the content of Mercury (Hg) in whitening surgery circulating in Batam City using the FIMS (Flow Injection Mercury System) test method. The results of research conducted on 10 whitening powder samples obtained mercury (Hg) levels with the largest average value, namely in the Px sample code with a value of 0.924 mg/kg, while the smallest average value was in the Lv sample code with a value of 0.021 mg/kg. In the test, there is a mercury content, but no one exceeds the maximum limit for cosmetics set by BPOM, which in BPOM regulations regarding metal contamination requirements in cosmetics containing mercury (Hg) is no more than 1 mg/kg, so it is safe to use. Keywords: Cosmetics, whitening powder, mercury, FIMS (Flow Injection Mercury System), Hg